Pneumolysin plays a key role at the initial step of establishing pneumococcal nasal colonization - Hotomi, Muneki; Yuasa, Jun; Briles, David E; Yamanaka, Noboru (Folia microbiologica, 2016)
Nasopharyngeal colonization by Streptococcus pneumoniae is an important initial step for the subsequent development of pneumococcal infections. Pneumococci have many virulence factors that play a role in colonization. Pneumolysin (PLY), a pivotal pneumococcal virulence factor for invasive disease, causes severe tissue damage and inflammation with disruption of epithelial tight junctions. In this study, we evaluated the role of PLY in nasal colonization of S. pneumoniae using a mouse colonization model. A reduction of numbers of PLY-deficient pneumococci recovered from nasal tissue, as well as nasal wash, was observed at days 1 and 2 post-intranasal challenges, but not later. The findings strongly support an important role for PLY in the initial establishment nasal colonization. PLY-dependent invasion of local nasal mucosa may be required to establish nasal colonization with S. pneumoniae. The data help provide a rationale to explain why an organism that exists as an asymptomatic colonizer has evolved virulence factors that enable it to occasionally invade and kill its hosts. Thus, the same pneumococcal virulence factor, PLY that can contribute to killing the host, may also play a role early in the establishment of nasopharynx carriage.
Keywords: streptolysiny; bakteriální proteiny; Streptococcus pneumoniae; faktory virulence; Mice, Inbred CBA; Carrier State; přenašečství; Animals; pneumokokové infekce; Female; ženské pohlaví; Streptolysins; Virulence Factors; Bacterial Proteins; myši inbrední CBA; zvířata; Pneumococcal Infections